CHARACTERIZATION OF COLLETOTRICHUM FALCATUM WENT. CAUSING RED ROT IN SUGARCANE SACCHARUM COMPLEX - P. C. ARADE; PUSHPENDRA SINGH; MAHESH MAHATMA (The Bioscan, 2014)
Red rot of sugarcane caused by Colletotrichum falcatum Went. is a serious problem which damaged the most of the important varieties. Various isolates of C. falcatum produced cottony, fluffy, fluffy cottony or suppressed growth on the PDA with colour range of grey, greyish black to greyish white. The isolate SGCF-8 showed maximum growth (87.34 mm) on PDA when incubated at 27±2ºC temperature for 10 days. The isolate SGCF5 was showed maximum sporulation (24.67 million spores/ml) while maximum dry mycelial weight was observed in isolate SGCF-1 (184.67mg) on PDB incubated at 27±2o C temperature for 15 days. The molecular characterization study was carried out by using five ISSR primers. The primer UBC-873 (92.30%) was showed the highest percentage of polymorphism with polymorphic information content (PIC) of 0.6853846. The dendrogram was showed isolate (SGCF-4) was situated separately with similarity matrix of 0.407 with SGCF-1. Other nine isolates were clustered in one group and sub-groups.